High prevalence of persistent parasitic infections in foreign-born, HIV-infected persons in the United States. - Natasha S Hochberg; Ruth N Moro; Anandi N Sheth; Susan P Montgomery; Frank Steurer; Isabel T McAuliffe; Yun F Wang; Wendy Armstrong; Hilda N Rivera; Jeffrey L Lennox; Carlos Franco-Paredes (Public Library of Science (PLoS), 2011)
Foreign-born, HIV-infected persons are at risk for sub-clinical parasitic infections acquired in their countries of origin. The long-term consequences of co-infections can be severe, yet few data exist on parasitic infection prevalence in this population.This cross-sectional study evaluated 128 foreign-born persons at one HIV clinic. We performed stool studies and serologic testing for strongyloidiasis, schistosomiasis, filarial infection, and Chagas disease based on the patient's country of birth. Eosinophilia and symptoms were examined as predictors of helminthic infection. Of the 128 participants, 86 (67%) were male, and the median age was 40 years; 70 were Mexican/Latin American, 40 African, and 18 from other countries or regions. Strongyloides stercoralis antibodies were detected in 33/128 (26%) individuals. Of the 52 persons from schistosomiasis-endemic countries, 15 (29%) had antibodies to schistosome antigens; 7 (47%) had antibodies to S. haematobium, 5 (33%) to S. mansoni, and 3 (20%) to both species. Stool ova and parasite studies detected helminths in 5/85 (6%) persons. None of the patients tested had evidence of Chagas disease (n = 77) or filarial infection (n = 52). Eosinophilia >400 cells/mm(3) was associated with a positive schistosome antibody test (OR 4.5, 95% CI 1.1-19.0). The only symptom significantly associated with strongyloidiasis was weight loss (OR 3.1, 95% CI 1.4-7.2).Given the high prevalence of certain helminths and the potential lack of suggestive symptoms and signs, selected screening for strongyloidiasis and schistosomiasis or use of empiric antiparasitic therapy may be appropriate among foreign-born, HIV-infected patients. Identifying and treating helminth infections could prevent long-term complications.